Pengaruh Media Pembelajaran Digital Terhadap Minat Belajar Anak Usia Dini - Erisa Dwi safitri; Wahyudi Wahyudi; Nurtina Irsad Rusdiani (Universitas Muhammadiyah Metro, 2024)
The aim of this research is to obtain data about the use of digital media and literacy classes together on student learning outcomes at RA Perwanida Lengkong, Sukorejo, Ponorogo. This research is quantitative research. The research instrument used to obtain data is a scale of digital learning media use and interest in learning. The data analysis technique used is descriptive statistical analysis.Data regarding the use of digital learning media on student learning outcomes was obtained through questionnaires by researchers by measuring something that has a relationship that: (1) There is a significant influence of the use of digital learning media on student learning outcomes. This is proven by obtaining a value of Fo = 9.109 and Sig. 0.000 < 0.05. Together, the variable use of digital learning media contributes 24.2% to the variable student learning outcomes. (2) There is a significant influence of the use of digital media on student learning outcomes. This is proven by the obtained value of tcount = 2.214 and Sig. 0.031 < 0.05. The variable use of digital learning media contributes 12.67% in improving student learning outcomes.